Price Determination in Public Procurement: A Game Theory Approach - Martin Schmidt (European Financial and Accounting Journal, 2015)
The article examines mechanism of bid price determination in public procurement by individual tenderers. A game theory approach is used to analyse this process. Firstly, a simple model with two firms illustrates the influence of expected opponent's decision in bid price setting. Assumptions are released subsequently and a game theory based model describes price determination under assumption of expected profit maximization. It is shown that the bid price depends on the costs associated with the performance of the contract and the expected number of bidders. The relationship between the amount of the bid price and the number of bids is also confirmed on the findings of several empirical studies that are quoted.
Keywords: H57; 650; Public procurement; Award procedure; Bid price; Game theory